Neuromuscular fatigue profile of prepubertal and adult female handball players - Papavasileiou, A.; Bassa, E.; Xenofondos, A.; Meletakos, P.; Noutsos, K.; Patikas, D.A. (Sports, 2025)
The investigation of the neuromuscular components of fatigue in team sports, especially in developmental ages, is limited. This study aimed to examine the neuromuscular fatigue and recovery patterns in prepubertal and adult female handball players, focusing on the soleus (SOL) and tibialis anterior (TA) muscles. Fifteen prepubertal (11.1 ± 0.9 years) and fourteen adult (22.0 ± 3.4 years) females performed a sustained isometric plantar flexion at 25% of maximal voluntary contraction (MVC) until exhaustion. The electromyographic (EMG) activity of the SOL and TA, torque, and central activation ratio (CAR) were recorded throughout the experiment. Endurance time was similar between groups (girls: 104 ± 93.5 s; women: 94.4 ± 30.2 s, p > 0.05), and both demonstrated progressive increases in muscle activation, without significant group differences for SOL and TA EMG (p > 0.05). Following fatigue, the torque and soleus (SOL) EMG activity decreased significantly compared to the pre-fatigue values in both groups (p < 0.001) and recovered (p > 0.05) in prepubertal and adult females within the first 3 and 6 min, respectively. The CAR remained unchanged over time, without significant differences observed between age groups (p > 0.05). These findings suggest that neuromuscular responses to fatigue are comparable between prepubertal and adult females, but recovery is significantly faster in prepubertal girls. Consequently, these findings underscore the need for age-specific recovery strategies in training programs, with tailored exercise-to-rest ratios to enhance performance and reduce fatigue during handball-specific activities.